THE IMPACT OF HEGEMONY ON RACISM IN J. M. COETZEES WAITING FOR THE BARBARIANS - SANDI KRISNA PERMADI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
This research discusses about contribution of hegemony to cause racism in J.M. Coetzee’s Waiting for the Barbarians. The analysis uses the theory of hegemony and racism. The method of this research is post-structural, which it integrates to objective approach as it intends to see the textual and chain it in inter-textual webs of the cases, facts and problems. For the data, it is taken from the citation of the action of hegemony and racism in the novel. For finding the impact of hegemony on racism, it should see the ideology of people with based by the consent of people. The action of people will refer to the cause of their consent. The problem of hegemony, it is like power of militarism that is based by the consent of people and pushes the happening of racial action which it is trigger by the hatred of people toward barbarians. The hatred of people influences their action with consent which it causes happening racialisation and racial discrimination. Key word : hegemony, militarism, racialisation, racial discrimination.